Metal halide perovskites for light-emitting diodes - Liu, Xiao-Ke; Xu, Weidong; Bai, Sai; Jin, Yizheng; Wang, Jianpu; Friend, Richard H.; Gao, Feng (Nature materials, 2021)
Metal halide perovskites have shown promising optoelectronic properties suitable for light-emitting applications. The development of perovskite light-emitting diodes (PeLEDs) has progressed rapidly over the past several years, reaching high external quantum efficiencies of over 20%. In this Review, we focus on the key requirements for high-performance PeLEDs, highlight recent advances on materials and devices, and emphasize the importance of reliable characterization of PeLEDs. We discuss possible approaches to improve the performance of blue and red PeLEDs, increase the long-term operational stability and reduce toxicity hazards. We also provide an overview of the application space made possible by recent developments in high-efficiency PeLEDs. The development of perovskite emitters, their use in light-emitting devices, and the challenges in enhancing the efficiency and stability, as well as reducing the potential toxicity of this technology are discussed in this Review.